Primary pancreatic-type acinar cell carcinoma of the jejunum with tumor thrombus extending into the mesenteric venous system: a case report and literature review - Takagi, Kosei (BMC Surg, 2017)
BACKGROUND: Although ectopic pancreatic tissue is common in the upper gastrointestinal tract, the incidence of ectopic pancreatic tissue in the jejunum is low, and malignant transformation in ectopic pancreatic tissue is rare. Furthermore, pancreatic-type acinar cell carcinoma (ACC) developing in the jejunum and ACC accompanied by tumor thrombus are extremely rare. CASE PRESENTATION: A 78-year-old-woman presented with melena. Abdominal computed tomography images and endoscopic examination revealed a submucosal jejunal mass with tumor thrombus extending into a jejunal vein. The patient underwent a curative resection combined with a partial jejunectomy and partial pancreatectomy. Histopathological examination of the resected tissue showed tumor cells with a homogeneous acinar architecture identical to pancreatic-type ACC and tumor thrombus. Postoperatively, she was followed for 10 months and had no recurrence. CONCLUSION: We present an extremely rare case of pancreatic-type ACC in the jejunum with extensive tumor thrombus invading into the mesenteric venous system. This type of cancer has not been reported previously but should be considered in the differential diagnosis of a jejunal mass.